Second-derivative UV spectral analysis of aqueous humor for eye disease diagnosis and assessing the effects of food additives on ocular health - Sherif S. Mahmoud; Shimaa M. Elshebley; Eman M. Aly; Sahar M. Awad; Gehan M. Kamal (Scientific Reports)
Abstract Ultraviolet absorption (UV) spectroscopy is an invaluable method for analyzing compounds in ocular fluids, identifying chemical structures, and understanding molecular interactions. The widespread use of additives in food production is well documented; these additives color, flavor, preserve, and enhance the texture or nutrition of food, ensuring a broader range of products and reducing costs. This study employed UV spectroscopy to examine changes in aqueous humor composition after daily intake of permitted amounts of food additives over 45–90 days. The rats were administered colorant dyes (carmoisine or tartrazine), a sodium benzoate preservative, or a combination of all three through oral gavage. Aqueous humor samples were collected post sedation from the anterior chamber via a 30-gauge needle without additional processing. The spectra of these samples were analyzed via secondary derivative calculations and chemometric analysis (principal component and hierarchical analyses) with OriginPro 2015 software. The common outcome observed was ocular toxicity, resulting from decreased antioxidant defense mechanisms, leading to ocular side effects on the cornea and lens. These changes in aqueous humor composition are indirectly linked to food additives rather than the mechanisms of aqueous humor formation.